What would Joey do? - Gantos, Jack (Square Fish, 2014)
Joey tries to keep his life from degenerating into total chaos when his mother sends him to be home-schooled with a hostile blind girl, his divorced parents cannot stop fighting, and his grandmother is dying of emphysema.